What makes professors credible: The effect of demographic characteristics and ideological beliefs - ZHU, Luke (Institutional Knowledge at Singapore Management University, 2016)
Five studies are conducted to examine how ideology and perceptions regarding gender, race, caste, and affiliation status affect how individuals judge researchers' credibility. Support is found for predictions that individuals judge researcher credibility according to their egalitarian or elitist ideologies and according to status cues including race, gender, caste, and university affiliation. Egalitarians evaluate low-status researchers as more credible than high-status researchers. Elitists show the opposite pattern. Credibility judgments affect whether individuals will interpret subsequent ambiguous events in accordance with the researcher's findings. Effects of diffuse status cues and ideological beliefs may be mitigated when specific status cues are presented to override stereotypes.